2005
DOI: 10.1088/0953-4075/38/8/009
|View full text |Cite
|
Sign up to set email alerts
|

Model sensitivity of theoretical results for ionization–excitation of helium

Abstract: The total cross section for ionization and simultaneous ionization–excitation of helium by electron impact has been revisited within the framework of first-order approximations for the projectile–target interaction. A systematic study of the sensitivity of theoretical results on the details of the computational model, specifically the treatments of the projectile–target interaction, the initial bound state and the ejected-electron–residual-ion interaction reveals the difficulties of making highly reliable pred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…However, even these theories did not do so well for the case of symmetric energy sharing [9]. In fact, even the calculation of the total He ionizationexcitation cross section remains a significant problem [10].…”
mentioning
confidence: 99%
“…However, even these theories did not do so well for the case of symmetric energy sharing [9]. In fact, even the calculation of the total He ionizationexcitation cross section remains a significant problem [10].…”
mentioning
confidence: 99%
“…times smaller cross sections compared to earlier absolute normalizations [26,27]. The previously available theoretical predictions (see [19] for a larger selection) are scattered and cannot resolve the problem. Our BSRMPS results, however, clearly favour the original normalizations [26,27].…”
mentioning
confidence: 93%
“…The magnitude of this cross section has been a widely debated issue over the years. A detailed analysis at the level of the firstorder approximation for the projectile-target interaction was carried out by Vorov and Bartschat [19]. They ultimately concluded that theoretical predictions for the ionizationexcitation process were extremely sensitive to the details of the model (in sharp contrast to ionization without excitation), and that highly sophisticated approaches would be required to make further progress.…”
mentioning
confidence: 99%